2016
DOI: 10.1055/s-0042-110790
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided biliary drainage or enteroscopy-assisted ERCP in patients with surgical anatomy and biliary obstruction: an international comparative study

Abstract: Background and study aims: How enteroscopy-assisted ERCP (e-ERCP) and endoscopic ultrasound-guided biliary drainage (EUS-BD) compare in patients with surgically altered upper gastrointestinal anatomy is currently unknown. The aims of this study were to compare efficacy and safety of both techniques and study predictors of these outcomes. Patients and methods: This was an international, multicenter comparative cohort study at 10 tertiary centers. Outcomes data included technical success (biliary access with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 16 publications
0
59
0
3
Order By: Relevance
“…As such, adverse events associated with EUS‐BD procedures remain important problems to be resolved. For example, a comparison of outcomes for enteroscopy‐assisted ERCP and EUS‐BD biliary tract treatments in patients with surgically altered gastrointestinal anatomy reported that the higher success rate for EUS‐BD (98% vs 65.3%) was associated with a significantly greater rate of adverse events (20% vs 4%) . Our results show that ERCP‐related procedures using a short SBE provided favorable outcomes with regard to the procedural success rate and the rate of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…As such, adverse events associated with EUS‐BD procedures remain important problems to be resolved. For example, a comparison of outcomes for enteroscopy‐assisted ERCP and EUS‐BD biliary tract treatments in patients with surgically altered gastrointestinal anatomy reported that the higher success rate for EUS‐BD (98% vs 65.3%) was associated with a significantly greater rate of adverse events (20% vs 4%) . Our results show that ERCP‐related procedures using a short SBE provided favorable outcomes with regard to the procedural success rate and the rate of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…2c,d) (Video S1). Although most CJs are treatable by BE‐ERCP or EUS‐guided procedure, 2–5 some cases require other approaches. To avoid invasive surgery, the piercing technique for cases of complete obstruction of CJs and the percutaneous route for taking the correct direction are useful.…”
Section: Brief Explanationmentioning
confidence: 99%
“…On the other hand, a systematic review of BE‐ERCP in patients with surgically altered anatomy showed an adverse event rate of 3.4%. Therefore, BE‐ERCP is clearly a less invasive and safer procedure than PTCD or EUS‐BD . Furthermore, as BE‐ERCP enables treatment of the causes of cholangitis such as bile duct stone or anastomotic stricture at a single session, it appears that BE‐ERCP is useful if the procedure is technically successful.…”
Section: Treatment Of Cholangitis In Patients With Surgically Alteredmentioning
confidence: 99%